PENGARUH KUALITAS PELAYANAN JASA KAMAR TERHADAP LOYALITAS PELANGGAN PADA HOTEL RATU MAYANG GARDEN PEKANBARU - Tedi Andika; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Service Quality is how far the difference between reality and expectations of consumers with the services they received or acquired. loyalty is described as the desire of consumers to subscribe to the company continuously, buying and using products and services repeatedly, and recommend the company's products to others. Under these conditions, a hospitality service company to be able to provide quality service to its customers, in order to create customer satisfaction that will lead the customer will be loyal to the products or services at the company.This research was conducted at Ratu Mayang Garden Hotel Pekanbaru is located on the roadJend Sudirmani Pekanbaru. The purpose of this research was conducted to determine the effect of service quality on customer loyality on Ratu Mayang Garden Hotel Pekanbaru.In this research methodology is descriptive and quantitative with SPSS, where samples were used that customer Ratu Mayang Garden Hotel Pekanbaru is a minimum stay of more than two times and as a source of information is the General Manager, Supervisor, and Front office. To determine the sample using the formula Slovin, sampling with purposive sampling method. Data collection through questionnaires and interviews.From the results of data analysis includes test validity, reliability, and simple linear regression, the quality of service in this study included five components of both the physical evidence, reliability, responsiveness, assurance, and caring. Each one has an indicator interrelated and positive effect on customer loyalty Ratu Mayang Garden Hotel Pekanbaru.Keywords: Service Quality, Customer Loyalty